Randomized Prospective Clinical Trial of Class II Restorations Using Low-shrinkage Flowable Resin Composite - Frascino, S. M. B. [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Silva, U. A. E. [UNESP]; Rahal, V [UNESP]; Barboza, A. C. S. [UNESP]; Santos, Paulo Henrique dos [UNESP]; Briso, André Luiz Fraga [UNESP] (Operative Dentistry Inc, 2020)
Purpose: The aim of this prospective, randomized, split-mouth clinical trial was to evaluate postoperative sensitivity, clinical performance, and interproximal contacts after using different restorative systems. Methods and Materials: Fifty-three subjects each received three class II restorations according to the restorative systems: conventional resin composite (PA: Peak Universal+Amelogen Plus, Ultradent), low-shrinkage flowable and nanoparticulate resin composites (ABF: Adper Single Bond 2+Filtek Bulk Fill Flow+Filtek Z350XT, 3M ESPE), and low-shrinkage flowable and microhybrid resin composites (XST: XP Bond+SDR+TPH3, Dentsply). Postoperative sensitivity was assessed at 24 hours, seven days, 90 days, and six months. The clinical performance and interproximal contacts were evaluated at baseline, six months, and one year. Friedman, Wilcoxon, Kruskal-Wallis, and Mann-Whitney tests were used to evaluate postoperative sensitivity and interproximal contacts. The equality test of two proportions and logistic regression analysis were used to assess the clinical performance. Results: No statistically significant differences were observed among groups for postoperative sensitivity. The highest spontaneous sensitivity was reported at 24 hours. ABF was the only group that did not present a reduction in cold sensitivity. Color, marginal discoloration, and superficial staining showed differences among the groups. XST did not show superficial staining after one year. No differences were observed among groups in relation to interproximal contacts. XST resulted in the loss of interproximal contact after one year. Conclusions: Different types of restorative systems do not influence postoperative sensitivity; however, ABF maintained cold sensitivity over time. Marginal discoloration occurred for all groups but occurred earliest for PA. XST presented a reduction of interproximal contact after one year of evaluation.